The Employment in Ukraine and the World: The Condition and Prospects - Gerasymenko, S. S.; Нerasymenko, V. V. (Statistics of Ukraine, 2023)
The article is devoted to analysis of tendencies in the employment, its patterns and determining factors in the world and selected countries, problems of the effective population’s employment and prevention of the massive unemployment. The high level of unemployment and large scales of the poverty, small numbers of job vacancies along with large numbers of unemployed per job vacancy are explicit negative features of the domestic and regional labor markets. A problem of special importance is the unemployment that has gained large scales in nearly all the strata of the population, worsened their welfare and life standards, to become a problem of global dimension. Analysis and solutions of unemployment problems have always drawn the increased attention of researchers in economics throughout the history of economic thought. The search for levers and tools allowing for eliminating this phenomenon with reliance on the total employment mechanism has been central to all the economic theories. A review of scientific developments focused on the essence and problems of unemployment shows the variety of approaches to the solution of problems associated with this phenomenon. In view of the above, assessment, modelling and forecasting of the labor market has a leading position in socio-economic studies. The article contains the author’s substantiation of the feasibility of assessment and analysis of the level and dynamics of unemployment as an important component of the labor market under the impact of factors such as the economic mode and its structural change, the technical and organizational level of entrepreneurship, the balance between the structure of production means and workforce, the overall performance of business management system. An analytical review and comparison of the contents of social programs for protection of unemployed in selected countries is made. The problem of assessment and determining the patterns of factor impact on the variations of unemployment level is addressed in the article on the basis of data on the dynamics of real gross domestic product and inflation, used for the aggregated assessment of the current performance of a national economy. It is recommended that the foundations of the policy on stabilization of prices, payment balance and structural transformations be developed in the future, given their impact on the employment and the income of the whole population and their groups, which consequence is supposed to be improvement of the labor market structure, unemployment reduction in particular. Determining the degree and vector of these measures’ impact on a national economy will be the next phase of the study.